Kajian Penerapan Ergonomi pada Rumah Tangga - I Gusti Agung Kd Desy Purnama Dewi; Desi Ernawati Lende (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Ergonomics is a final result that ergonomics itself wants to achieve. Ergonomics is defined as an effort in the form of science, technology, and art to harmonize equipment, machines, work, systems, organizations and the environment with human abilities, expertise, and limitations so that a healthy, safe, comfortable, efficient and productive condition and environment is achieved, through optimal and maximum functional utilization of the human body (Manuaba, 2000). Home is a basic need for every human being, this is in accordance with the concept of basic human needs, namely clothing, food and shelter. Kitchens built in simple houses generally only meet the requirements for having a kitchen. Even the height of the kitchen work table and the height of the cupboard for equipment vary according to the taste of the carpenter or bricklayer. Thus, safe, comfortable, healthy and efficient working conditions can be achieved. In the case of incompatibility of work tools with body ergonomics, it can be overcome with appropriate technology. Most importantly, from the beginning of kitchen planning, ergonomics must be included so that the working environment and conditions can be made effective and efficient for its users.